2017
DOI: 10.3928/01484834-20170421-04
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Gaming Simulation in Nursing Education: A Focus Group Study

Abstract: Virtual gaming simulation can provide experiential learning opportunities that promote engagement and allow learners to acquire and apply new knowledge while practicing skills in a safe and realistic environment. [J Nurs Educ. 2017;56(5):274-280.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 32 publications
2
37
1
5
Order By: Relevance
“…Results from an earlier focus group study suggested that this VGS enhanced student engagement, learning acquisition, and satisfaction (Verkuyl et al, 2017a). During data collection, the research team noted that the participants used the focus group as a way to debrief their experience (Verkuyl et al, 2017a). The need for debriefing virtual simulation experiences is supported by the literature (Peters & Vissers, 2004;Tilton, Tiffany, & Hoglund, 2015); the question now is how best to conduct the debrief.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from an earlier focus group study suggested that this VGS enhanced student engagement, learning acquisition, and satisfaction (Verkuyl et al, 2017a). During data collection, the research team noted that the participants used the focus group as a way to debrief their experience (Verkuyl et al, 2017a). The need for debriefing virtual simulation experiences is supported by the literature (Peters & Vissers, 2004;Tilton, Tiffany, & Hoglund, 2015); the question now is how best to conduct the debrief.…”
Section: Introductionmentioning
confidence: 99%
“…Some members of our research team designed a VGS on the topic of mental health and embedded it in the first-year curriculum of a baccalaureate program (see VGS at https:// de.ryerson.ca/games/nursing/mental-health/). The VGS was designed as an interactive and experiential opportunity for nursing students to conduct a mental health and interpersonal violence assessment while engaging in clinical decision making during a simulated home visit (Verkuyl et al, 2017a). The learner was given feedback at each of the 13 decisions points, as well as a summary report of each decision was made with links to educational content at the end of the VGS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing students can emulate the roles of registered nurses and provide therapeutic care to a virtual patient in the same way they would with a real-life patient based on information provided during simulation (Padilha et al, 2019). The integration of virtual simulation into nursing pedagogy fits with the new generation of nursing students' learning needs (Verkuyl et al, 2017). Reported advantages of nursing students using virtual simulation include providing a safe, nonthreatening practice environment (Cobbett & Snelgrove-Clarke, 2016), offering flexible and reproducible learning experience (Peddle et al, 2016), and catering to a large number of learners simultaneously (Sok Ying et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When debriefing is noted, it is an assumed activity, and few details are provided. In a previous study evaluating the effectiveness of VGS, we found participants using focus groups to debrief their simulation experience (Verkuyl et al, 2017a). Gordon (2017) provided a commentary of his design and implementation of web-based conferencing to debrief asynchronous virtual simulations.…”
Section: Introductionmentioning
confidence: 99%